Valuing dynamic capabilities-based synergies with real options - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2021)
Acquisition-based dynamic capabilities have become well established as a new imperative for organizing mergers and acquisitions (M&A) processes. However, understanding the full benefits and possible limits of real options applications to measure a dynamic capability-based synergy in M&A deals remains a challenge. This paper draws on real options theory to explore some of these benefits and limits to value a synergy in two highly strategic M&A deals. More specifically, the author develops the proposition that justifies the role of dynamic capabilities as antecedents of the success of M&A deals in the information and communications technology industry and demonstrates real options application to measure M&A synergies.
Keywords: 330; acquisition; business model; dynamic capabilities; real options; synergy; the ICT industry